2020
DOI: 10.1111/jopy.12584
|View full text |Cite
|
Sign up to set email alerts
|

When guiding principles do not guide: The moderating effects of cultural tightness on value‐behavior links

Abstract: Objective Ample research documented the effects of guiding principles in people's lives, as reflected in personal values, on a variety of behaviors. But do these principles universally guide behaviors across all cultural contexts? To address this question, we investigated the effect of cross‐cultural differences in the strength of social norms (i.e., tightness‐looseness) on value‐behavior relationships. Method Using the archival data from the World Value Survey for 24 nations (N = 38,924; 51.40% female; Mage =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 63 publications
(113 reference statements)
1
21
0
Order By: Relevance
“…It could be that messages referring to peoples' personal moral values had a better effect on their intentions in the 'loose' culture, as it is more permissible to realise personal motivations, rather than motivations that align with the group interest. This finding is in line with the recent observation that the link between personal values and behaviour is much more prominent in loose cultures, as in these cultures people are less restricted by social norms and are more likely to be driven by their personal norms (Elster & Gelfand, 2021).…”
Section: Discussionsupporting
confidence: 91%
“…It could be that messages referring to peoples' personal moral values had a better effect on their intentions in the 'loose' culture, as it is more permissible to realise personal motivations, rather than motivations that align with the group interest. This finding is in line with the recent observation that the link between personal values and behaviour is much more prominent in loose cultures, as in these cultures people are less restricted by social norms and are more likely to be driven by their personal norms (Elster & Gelfand, 2021).…”
Section: Discussionsupporting
confidence: 91%
“…Research in samples from the United States, Australia, and Japan suggests a strong tendency to evaluate the self more favorably than others (Haslam et al, 2005;Sedikides et al, 2003;Valdesolo & DeSteno, 2008); here, we highlight that cultural dynamics, especially how people understand themselves in relation to social others, might influence the magnitude of self-interest bias and mitigate self-favorable judgments in normative behavioral domains. The findings may help illuminate factors that influence the magnitudes of self-other discrepancies (e.g., Haslam et al, 2005;Sedikides et al, 2003) and attitude-behavior gaps (e.g., Dong et al, 2020;Elster & Gelfand, 2020) in self-interest-related judgments.…”
Section: Theoretical and Practical Implicationsmentioning
confidence: 91%
“…The moderating effect of cultural tightness/looseness on the relationship between values and behavior has been recently investigated empirically (Elster & Gelfand, 2020). The researchers investigated the moderating effect of cultural tightness/looseness (as reported in Gelfand et al, 2011) on relationships between personal values and self-reported behaviors, as assessed in archival data.…”
Section: Mechanisms That Induce External Controlmentioning
confidence: 99%